Variables Perceived by Managers as Antecedents That Lead Firms to Environmental Management: An Empirical Research in the Turkish Construction Sector - Bekiroglu, Caglar; Erdil, Oya; Alpkan, Lutfihak (Elsevier Science Bv, 2011)
Environmental issues have constituted problems that effect simultaneously all humans, nations and firms. Their effects are widened by the time. To protect the natural environment and to offer a sustainable future to the next generation have become a common target for humanity. As far as countries are concerned, preventing foreign-source dependence with respect to limited resources has become a more important objective by the time. It is being observed that especially firms which have recognized that they can not achieve the desired results through cost competition have recently turned their faces toward environmental management as a new competition strategy. It is possible that the firms create new markets and ensure competitive advantage through protection of the natural environment. The main objective of this study is to examine what the managers perceive as antecedents that lead firms to environmental management. This is at the same time the originality of the present study. These antecedents that may be considered as the first chain of previous studies, make a complementary and integral contribution to the incomplete part. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility 7th International Strategic Management Conference
7th International Strategic Management Conference -- JUN 30-JUL 02, 2011 -- Paris, FRANCE
Keywords: Environmental management; national environmental characteristics; eco-efficiency; firm past performance; environmental sensitivity